2017
DOI: 10.5603/fm.a2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the lumbar vertebrae in the Turkish population using three-dimensional computed tomography: correlation with sex, age, and height

Abstract: (Folia Morphol 2017; 76, 3: 433-439)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…Height explained a greater amount of the variability in PD at all lumbar vertebral levels. These findings support the prior studies Gulec [10].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Height explained a greater amount of the variability in PD at all lumbar vertebral levels. These findings support the prior studies Gulec [10].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have demonstrated positive correlation between some of these variables. One such study using digital caliper measurement of PD in cadavers showed that taller and heavier subjects had statistically significant larger PD [10]. A similar CT based study on a Turkish population demonstrated that transverse PD values are directly proportional to subject height [11].…”
Section: Introductionmentioning
confidence: 96%
“…While focusing on the reasons of the narrow spinal canal, few studies has been conducted on LP so mean lateral elements of the vertebra. (5)(6)(7)(8)(9)(10)(11). They demonstrated that significant differences value of LP between variability including ethnicity, age, gender, height and weight and vertebral levels.…”
Section: Discussionmentioning
confidence: 97%
“…But degenerative changes in vertebral bone elements such as lumbar pedicle (LP) have not been so investigated in LSCS yet. However for effective and healthy lumbar stabilization LP morphology has been investigated in many studies and it has been proved that LP mostly shows anatomic variabilities (5)(6)(7)(8)(9)(10)(11). Base on these datas, we aimed to investigate the relationship of LP thickness (LPT) with LSCS using MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Yu, et al [8], have shown significant correlation between lumbar pedicle morphometry, gender, height and weight utilizing digital calipers on a population of American human cadavers. Gulec, et al [9], have utilized three-dimensional CT to compare gender, age and height with pedicle morphometry in a Turkish only population. Another study utilized electronic calipers to compare the pedicles in a small (12 specimen) Greek only cadaveric study [10].…”
Section: Introductionmentioning
confidence: 99%